2013
DOI: 10.1159/000348703
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Distribution as a Risk Factor for Cerebrovascular Disease: An MRI-Based Body Fat Quantification Study

Abstract: Background: While adiposity is a well-established risk factor for cardiovascular disease, the association between adiposity and cerebrovascular disease is not entirely understood. For example, common methods to quantify body fat volume such as body mass index, waist circumference and waist-to-hip ratio are not suitable to identify the complex distribution patterns of body fat and its relation to cerebrovascular pathology. In view of a better understanding of the association between fat distribution and cerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 37 publications
1
44
1
1
Order By: Relevance
“…Similarly, those in the lowest compared to the highest 10% of aerobic fitness were found to have a 70% increased risk of ischemic stroke, while the risk was more than doubled for hemorrhagic stroke. Several previous studies have linked BMI and visceral adiposity, and aerobic fitness, to clinical manifestations of atherosclerotic disease, but predominantly in older populations and for the outcomes of cardiovascular disease and death [21,22,23,24]. The results of the present study indicate that classic risk factors for atherosclerotic disease assessed already in adolescence contribute substantially to an increased risk of stroke.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, those in the lowest compared to the highest 10% of aerobic fitness were found to have a 70% increased risk of ischemic stroke, while the risk was more than doubled for hemorrhagic stroke. Several previous studies have linked BMI and visceral adiposity, and aerobic fitness, to clinical manifestations of atherosclerotic disease, but predominantly in older populations and for the outcomes of cardiovascular disease and death [21,22,23,24]. The results of the present study indicate that classic risk factors for atherosclerotic disease assessed already in adolescence contribute substantially to an increased risk of stroke.…”
Section: Discussionsupporting
confidence: 56%
“…Nagura et al [26] reported that extreme accumulation of visceral fat as measured by abdominal CT was more likely associated with lacunar infarcts. Other CT-based studies have suggested that visceral fat accumulation was related to the presence of white matter hyperintensities and silent lacunar infarction on brain MRI [9,10,27] . However, whether this association was mediated by adiposity-related risk factors for cerebral small vessel diseases, such as hypertension or dia- Recent studies have demonstrated that VAT accumulation was positively associated with cardiovascular diseases [10,28,29] and that VAT produces large amount of interleukin-6 and by doing so promotes the secretion of C-reactive protein, inflammatory markers, and adipocytokines [14,30] .…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, peripheral subcutaneous fat may be protective in nature with respect to cardiovascular diseases [31] . Therefore, the percentage of VAT in total adipose tissue has recently been proposed as having the potential as a sensitive parameter showing highly significant correlations with the markers of cardiovascular disease [10] . The strength of our study was that we used abdominal CT for measuring abdominal fat distribution in subjects who underwent brain MRI; therefore, we could demonstrate that VAT/SAT ratio has potential as a new epidemiological predictor of CMB in neurologically healthy people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that visceral adiposity induces structural and functional changes in the brain. Furthermore, brain imaging studies in individuals with or without stroke history suggest that visceral adiposity can be a risk factor for cerebrovascular diseases, because visceral fat accumulation and an increased ratio of visceral adipose tissue to total adipose tissue strongly correlate with white matter lesions and ischemic lesions (Karcher et al, 2013;Nagura et al, 2004;Yamashiro et al, 2014). In addition to being a risk factor, visceral adiposity may have an influence on brain damage following acute ischemic insult, especially in the aged brain.…”
Section: Introductionmentioning
confidence: 99%